Natural Enemies of the Frankliniella Complex Species (Thysanoptera: Thripidae) in Ataulfo Mango Agroecosystems. Issue 1 (5th August 2015) - Rocha, Franklin H.; Infante, Francisco; Castillo, Alfredo; Ibarra-Nuñez, Guillermo; Goldarazena, Arturo; Funderburk, Joe E.
Abstract : A field survey was conducted in Ataulfo mango ( Mangifera indica L.) orchards in Chiapas, Mexico, with the objective of determining the natural enemies of the Frankliniella complex species (Thysanoptera: Thripidae). Seven species of this genus feed and reproduce in large numbers during the mango flowering. Two representative orchards were selected: the orchard "Tres A" characterized by an intensive use of agrochemicals directed against thrips, and the orchard "La Escondida" that did not spray insecticides. During mango flowering, five inflorescences were randomly collected every 5 d in both orchards, for a total of 18 sampling dates. Results revealed the presence of 18 species of arthropods that were found predating on Frankliniella . There were 11 species in the families Aeolothripidae, Phlaeothripidae, Formicidae, Anthocoridae and Chrysopidae; and seven species of spiders in the families Araneidae, Tetragnathidae, and Uloboridae. Over 88% of predators were anthocorids, including, Paratriphleps sp. (Champion), Orius insidiosus (Say), Orius tristicolor (White), and O. perpunctatus (Reuter). The orchard that did not spray insecticides had a significantly higher number of predators suggesting a negative effect of the insecticides on the abundance of these organisms.